Penggunaan Media Sosial dalam Kampanye Pemilihan Gubernur dan Wakil Gubernur Jawa Tengah Tahun 2013 - Andudei Hardyanta Husada Dompas; Rina Martini; Nunik Retno H (Journal of Politic and Government Studies, 2014)
Social media is an effective and efficient media because it’s able to give informations about the candidates in the local election widely and in a faster way, so the appearance of social media as a campaign tools in local election becomes one of the modern way to increase popularity and electability of the candidates. This research is objected to describe the use of social media in election campaign for Governor and Vice Governor of Central Java in 2013 and to describe the political messages socialized by each candidates through social media. This research used descriptive qualitative research method which the data are collected from interview with the representative of the campaign team from each candidate pairs and voters who use social media and documentation of social medias that are used in the campaign period.   The results of this research indicate that the use of social media is considered as one of the important campaign instrument because it is simple yet can reach the young voters and mid to high class citizens, it is also can spread the news about the candidates faster. Each candidate pairs used 4 kind of social media, those are Websites, Twitter, Facebook and Youtube. The political messages which is communicated by each candidates are generally mean to build their image, persuade the people to vote them, and informing achievements, vision and mission or main programs. The success of this social media campaign is depend on the citizen’s characteristic, whether the citizens active in social media or not. Beside that the campign’s activeness and candidate’s popularity in social media isn’t always help the candidate to gain the highest votes, there are other factor that help the candidate to win the election, such as the party political machine.  This research recommends that each candidates should use variative campaign instruments, not only counting on the social media because it haven’t became massive yet in the local area. The campaign teams and each candidate pairs have to see the voters’ character before building the campaign strategy, so the  campaign will work properly.Keywords: campaign, candidate, social media, political message